Comparative Genomic and Phylogenetic Analysis of Chloroplast Genomes of Hawthorn (Crataegus spp.) in Southwest China - Wu, Xien; Luo, Dengli; Zhang, Yingmin; Yang, Congwei; Crabbe, M. James C.; Zhang, Ticao; Li, Guodong (Frontiers in Genetics, 2022)
The hawthorns (Crataegus spp.) are widely distributed and famous for their edible and medicinal values. There are ~18 species and seven varieties of hawthorn in China distributed throughout the country. We now report the chloroplast genome sequences from C. scabrifolia, C. chungtienensis and C. oresbia, from the southwest of China and compare them with the previously released six species in Crataegus and four species in Rosaceae. The chloroplast genome structure of Crataegus is typical and can be divided into four parts. The genome sizes are between 159,654 and 159,898bp. The three newly sequenced chloroplast genomes encode 132 genes, including 85 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Comparative analysis of the chloroplast genomes revealed six divergent hotspot regions, including ndhA, rps16-trnQ-UUG, ndhF-rpl32, rps16-psbK, trnR-UCU-atpA and rpl32-trnL-UAG. According to the correlation and co-occurrence analysis of repeats with indels and SNPs, the relationship between them cannot be ignored. The phylogenetic tree constructed based on the complete chloroplast genome and intergenic region sequences indicated that C. scabrifolia has a different origin from C. chungtienensis and C. oresbia. We support the placement of C. hupehensis, C. cuneata, C. scabrifolia in C. subg. Crataegus and C. kansuensis, C. oresbia, C. kansuensis in C. subg. Sanguineae. In addition, based on the morphology, geographic distribution and phylogenetic relationships of C. chungtienensis and C. oresbia, we speculate that these two species may be the same species. In conclusion, this study has enriched the chloroplast genome resources of Crataegus and provided valuable information for the phylogeny and species identification of this genus.